Just-in-Time (JIT) Inventory Management in Cold Chains: A Strategy for Mitigating Perishable Goods Waste - Mweshi, Geoffrey Kapasa; Kabamba, Daniel; Nguluwe, Chaponga (Archives of Business Research, 2025)
The growing global issue of food waste, especially within the supply chain of perishable goods, calls for innovative logistical strategies. This paper investigates the use of Just-in-Time (JIT) inventory management as a strategic approach to reduce waste and improve efficiency in cold chains. Conventional logistics models typically depend on large buffer inventories, which heighten the risk of spoilage and related financial losses. In contrast, JIT emphasizes the exact synchronization of product delivery with immediate demand, thereby significantly decreasing storage durations and the chances of product deterioration. The study explores how the incorporation of Internet of Things (IoT) technologies—such as real-time sensors for temperature, location, and humidity—is crucial for the effective execution of a JIT system. These technologies offer the necessary data visibility and predictive analytics needed to enhance transportation routes, accurately forecast demand, and facilitate automated decision-making. Through an extensive literature review and case study evaluation, this paper illustrates that JIT, when bolstered by IoT, converts the cold chain from a static, reactive framework into a dynamic, proactive network. The results indicate that this methodology not only significantly reduces waste in perishable goods but also enhances overall supply chain resilience and profitability, presenting a feasible route towards more sustainable and efficient logistics operations.